Supporting the education of engineering mathematics using the immediate feedback method - Sipos, Dóra; Kocsis, Imre (Teaching Mathematics and Computer Science, 2023)
In the literature, several methods are suggested to deal with problems regarding the efficiency of mathematics education including techniques that help integrate new knowledge into long-term memory. We examined how effective the application of the immediate feedback method is in teaching engineering mathematics. The article presents the method used and the results obtained during the study. Subject Classification: 97D40, 97D60